Modeling and control of photovoltaic panels base perturbation and observation MPPT method - Palizban, O.; Mekhilef, S. (2011 IEEE International Conference on Control System, Computing and Engineering, 2011)
Nowadays renewable energy is important and environmentally friendly, as it does not pollute and costs little. Solar energy is one of the main photovoltaic system types of energy. For those with no access to the main network due to geographical location, this kind of energy is beneficial and valuable in providing the needed electrical energy. This paper presents photovoltaic system modeling, temperature, its variation and irradiation, and how the system connects to the DC bus via a DC/DC converter. It has the ability to follow maximum power point tracking (MPPT) by a special control circuit, something useful in hybrid systems. Finally, an inverter is used to transfer power to the AC network and decrease the harmonic in the connection point.